Efficacy of Dialectical Comprehensive Treatment of Traditional Chinese Medicine in Patients with Chronic Stable Heart Failure: A Randomized Controlled Trial - Lixiang Yang; Yuanyuan Chen; Fei Lou; Xiaoxia Zhao; Jia Zhou (Cardiology Research and Practice)
The treatment of chronic stable heart failure (CSHF) with integrated traditional Chinese and Western medicine has been of wide concern. We mainly discuss the clinical efficacy of TCM decoction combined with acupuncture and moxibustion (A&M) in CSHF treatment on the basis of syndrome differentiation and treatment (SDT). The control group was given conventional cardiac rehabilitation (CCR), and the treatment group was given TCM decoction combined with A&M treatment based on SDT on the basis of conventional cardiac rehabilitation. The clinical efficacy and cardiopulmonary exercise testing (CPET) indicators were evaluated. Left ventricular ejection fraction (LVEF), NT-proBNP, myocardial ischemia threshold (MIT), and 6-minute walking distance (6MWD) were measured by ultrasound, ELISA, electrocardiogram, and 6MWD test. After treatment, the clinical efficacy, LVEF, and 6MWD of the treatment group were better than in the control group. The NT-proBNP plasma level and MIT in the treatment group were lower than in the control group. The treatment group had enhanced AT, VO2 Peak, VO2 Peak/HR, and Peak power and decreased resting systolic pressure and peak systolic pressure, and the difference was statistically significant. Dialectical comprehensive treatment of TCM could effectively improve cardiac function and clinical treatment effect, which was worthy of clinical application.